MULTIKULTURALISME DALAM SEJARAH: DARI MASA KLASIK HINGGA MASA MODERN - Sahril Chaniago, Chairunnisa; Albina, Meyniar (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
This research uses library research whose data sources are obtained from several books and documentation materials, magazines, journals, and newspapers. This research aims to examine the development of multiculturalism from classical to modern times. The results explain that multiculturalism has an important role to maintain harmony and peace in the world. There are also several factors that cause the emergence of multicultural societies, including geographical factors, cultural influences from outside, inter-tribal marriages, and climate differences. Over time, multiculturalism has evolved to play an important role in the formation of sosial and political identities in diverse societies. This research concludes that although challenges in the application of multiculturalism persist, the concept remains relevant in creating an inclusive and harmonious society in the modern era